Electrolytic treatment and biosurfactants applied to the conservation of Eugenia uniflora fruit - Dilarri, Guilherme [UNESP]; da Silva, Vinicius Luiz [UNESP]; Pecora, Hengli Barbosa [UNESP]; Montagnolli, Renato Nallin [UNESP]; Corso, Carlos Renato [UNESP]; Bidoia, Ederio Dino [UNESP] (My University, 2016)
Microorganisms are the primary responsible for food poisoning and food spoilage. The purpose of this study was to evaluate different fruit washing methods with tap water, electrolyzed water and rhamnolipids solution produced by Pseudomonas aeruginosa LBI, in order to inhibit microbial growth. The tested organism was Eugenia uniflora. The fruits were washed and periodically inoculated into culture media to evaluate and count the colonies on the fruit surface. It was also observed the deterioration level of the fruits after each treatment. The results showed that treatment with rhamnolipids were the most efficient, inhibiting the growth of fungi and bacteria. The electrolyzed water proved to be very efficient in bacterial inhibition at the initial time, but in the final time it did not present any inhibitory effect. The electrolyzed water was also not effective in eliminating fungus. Washing with tap water was the less efficient treatment of all. The only treatment that showed an increased durability has been with rhamnolipids, increasing shelf life by up to two days. Thus rhamnolipids are the most recommended method for fruits sanitation.
Keywords: Electrolyzed water; Food; Microorganism; Pseudomonas aeruginosa; Rhamnolipid